Ramadan during pregnancy and the role of dietary intake for neonatal health in Kaduna, Northwestern Nigeria: a cross-sectional study - Musa Abubakar Kana; Bilkisu Usman; Amina Mohammed-Durosinlorun; Jennifer Ahmed; Hassana Habiba Abubakar; Yakub Abdulmalik; Fabienne Pradella (BMC Pregnancy and Childbirth)
Abstract Background Ramadan during pregnancy is associated with adverse offspring health outcomes. Recent evidence from Europe indicates that maternal diet during non-fasting hours might alleviate these effects. This study describes fasting, diet, and sleep habits among pregnant Muslims in Kaduna, Nigeria, and assesses impacts on neonatal health in this setting. Methods Between July 2023 and February 2024, we conducted 1814 interviews with women whose pregnancy overlapped with Ramadan 2023 in Kaduna, northwestern Nigeria (cross-sectional study). We used a structured questionnaire to collect data on fasting, diet and sleep during Ramadan, as well as maternal socio-demographic characteristics. In the analyses of birth outcomes, 1370 mother-newborn pairs were included. We performed multivariate regression analyses to evaluate associations between fasting and birth weight and gestational duration, as well as the interaction of fasting with maternal dietary intake and sleep patterns. Results More than 80% of the study participants fasted during pregnancy. Women who fasted had infants with lower birth weights than non-fasting participants (-90.38 g, 95% CI: -173.64 g to -6.12 g). No independent associations were detected between reduced sleep and food intake, and birth weight. Fasting was not associated with gestational duration. Negative effects of fasting on birth weight were consistently concentrated among participants who reduced their dietary or fluid intake during Ramadan. Conclusions Dietary intake during non-fasting hours might mitigate potential adverse effects of Ramadan fasting on birth weight. With more than 25% of the global population adhering to Islam, this study highlights the need for additional research on Ramadan during pregnancy across different settings.